Peningkatan Kompetensi Guru dalam Analisis Data Hasil Pembelajaran dengan Metode Statistika Menggunakan Microsoft Excel di SD Muhammadiyah 1 Trenggalek: Improving Teachers’ Competence in Analyzing Learning Outcomes Data Using Statistical Methods with Microsoft Excel at SD Muhammadiyah 1 Trenggalek - Rifada, Marisa; Saifudin, Toha; Kurniawan, Ardi; Ramadhani, Azzah Nazhifa Wina; Maharani, Prima; Sentosa, Martha Ayu (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Muhammadiyah 1 Trenggalek Elementary School is one of the leading private elementary schools in Trenggalek Regency that implements an innovative system in its learning and has a strong commitment to improving the quality of education. However, most of the teachers in this elementary school still lack understanding of the concept of statistics along with the application of technology to analyze student learning data, so that the evaluation of student learning outcomes becomes less than optimal. Therefore, this community service program is carried out to provide intensive training on basic understanding of statistics, the use of Microsoft Excel to process data, and the application of analysis results to improve teaching methods. This program was carried out through several stages, consisting of providing offline training and assistance to groups of teachers in applying the training results to student learning data. The evaluation results show an increase in teacher understanding of the training material provided, with evidence of an increase in the average pre-test score of 64.46 to 71.08 in the post-test. Thus, this community service activity can be said to have succeeded in increasing teacher competence in using Microsoft Excel as a means of analyzing student learning data, which is also a start to improving the quality of Muhammadiyah 1 Trenggalek Elementary School teachers.